The Cap Snatching of Segmented Negative Sense RNA Viruses as a Tool to Map the Transcription Start Sites of Heterologous Co-infecting Viruses - Lin, Wenzhong; Qiu, Ping; Jin, Jing; Liu, Shunmin; Ul Islam, Saif; Yang, Jinguang; Zhang, Jie; Kormelink, Richard; Du, Zhenguo; Wu, Zujian (Frontiers in Microbiology, 2017)
Identification of the transcription start sites (TSSs) of a virus is of great importance to understand and dissect the mechanism of viral genome transcription but this often requires costly and laborious experiments. Many segmented negative-sense RNA viruses (sNSVs) cleave capped leader sequences from a large variety of mRNAs and use these cleaved leaders as primers for transcription in a conserved process called cap snatching. The recent developments in high-throughput sequencing have made it possible to determine most, if not all, of the capped RNAs snatched by a sNSV. Here, we show that rice stripe tenuivirus (RSV), a plant-infecting sNSV, co-infects Nicotiana benthamiana with two different begomoviruses and snatches capped leader sequences from their mRNAs. By determining the 5′ termini of a single RSV mRNA with high-throughput sequencing, the 5′ ends of almost all the mRNAs of the co-infecting begomoviruses could be identified and mapped on their genomes. The findings in this study provide support for the using of the cap snatching of sNSVs as a tool to map viral TSSs.